2015
DOI: 10.1080/01621424.2015.1092909
|View full text |Cite
|
Sign up to set email alerts
|

Self-Management of Heart Disease in Older Adults

Abstract: The American Heart Association estimates that 81% of people who die of coronary heart disease are 65 years old or older. The leading risk health behaviors include physical inactivity, poor diet, smoking and binge drinking. Using the 2011-2012 California Health Interview Survey (CHIS), this study looked at how self-management, which includes a plan developed by a medical professional and the confidence to manage one's disease, may decrease negative risk behaviors in older adults. The presence of a plan and incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…These findings indicate that participants are becoming more empowered and support the conceptualisation of health literacy as an instrument in the empowerment process [ 45 ]. Other studies [ 46 ] have examined specifically the role of self-efficacy and health literacy in improving health outcomes and also advocate the need for self-management programmes to promote the development of self-efficacy. Numerous studies have postulated the links between self-efficacy, health literacy and self-care behaviours [ 8 , 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings indicate that participants are becoming more empowered and support the conceptualisation of health literacy as an instrument in the empowerment process [ 45 ]. Other studies [ 46 ] have examined specifically the role of self-efficacy and health literacy in improving health outcomes and also advocate the need for self-management programmes to promote the development of self-efficacy. Numerous studies have postulated the links between self-efficacy, health literacy and self-care behaviours [ 8 , 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…While age is shown to be independently associated with inflammation and a risk for CVD, health behaviors may also complicate these factors. Health behaviors that are commonly linked with poor outcomes in CVD patients include inactivity, poor nutrition, and smoking [65,66]. The AHA reported that these health behaviors, in addition to poor sleep behavior, are all associated with higher risk for development of CVD [6] Self-management of these health behaviors, under the direction of medical care specialists, have shown promise in CVD patients.…”
Section: Management and Treatment Of Cvd In Older Adultsmentioning
confidence: 99%
“…In order to reduce the burden of medical prevention and disease management, it is of great practical significance for patients to play a full role in the long‐term management. Patients adjust to the changes of physical and psychological, and they also need to improve behaviours related to secondary prevention, such as monitoring signs and symptoms, incorporation of key medications, adhering to treatment and keep healthy lifestyle (Dorje et al., 2018 ; Huynh‐Hohnbaum et al, 2015 ). These behaviours are referred to self‐management.…”
Section: Introductionmentioning
confidence: 99%